Web Based Information System for Bus Rapid Transit (BRT) Trans Cirebon - Dewi, Wiwiek Nurkomala; Liesen, Daimend Dhemaz; Kusnadi, Kusnadi (Proceeding International Conference on Religion, Science and Education, 2026)
Bus Rapid Transit (BRT) Trans Cirebon is a public transportation system initiated to improve urban mobility in Cirebon City, Indonesia. Despite its growing importance, public access to accurate and up-to-date information about routes, schedules, fares, and facilities remains limited, resulting in low passenger engagement. This research aims to design and develop a web-based information system that provides centralized, accessible, and real-time information on BRT Trans Cirebon services. The system was developed using the Waterfall methodology, encompassing stages of requirements definition, system design, implementation, integration, and testing. Data were obtained through literature review, interviews with BRT administrators, and field observations. The system design utilized Unified Modeling Language (UML) diagrams—use case, activity, sequence, and class diagrams—to model functionality and user interactions. The implementation was carried out using PHP, HTML, CSS, and JavaScript, supported by a MySQL database and XAMPP as the local server environment. The resulting website includes modules for route information, schedules, feedback submission, and administrative management. System testing was performed using the Black Box method to ensure functional reliability and user accessibility. The developed website successfully enhanced information delivery efficiency, providing easy access for users through desktop and mobile devices. Evaluation results indicate a positive user response, highlighting improved accessibility, accuracy, and user satisfaction in obtaining BRT service information. This research contributes to the digital transformation of urban public transport services in regional cities, offering a model for information system development that integrates accessibility, responsiveness, and data accuracy.